2020
DOI: 10.2169/internalmedicine.5614-20
|View full text |Cite
|
Sign up to set email alerts
|

Non-COVID-19 Patients with Life-threatening Diseases Who Visited a Fever Clinic: A Single-center, Observational Study in Tokyo, Japan

Abstract: Objective In fever clinics screening coronavirus disease (COVID-19), there could be patients with life-threatening diseases that physicians should not overlook. We exploratorily investigated the final diagnosis among non-COVID-19 hospitalized patients who visited the fever clinic. Methods This was a retrospective, observational, and single-centered study conducted in the National Center for Global Health and Medicine (NCGM), Tokyo, Japan. We conducted a retrospective ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…However, oral, pharyngeal and cervical infections (e.g., PA, tonsillitis, acute epiglottitis, deep neck abscess) may be overlooked if a thorough oral and pharyngo-laryngeal evaluation is avoided due to the high transmissibility of COVID-19. Akiyama et al ( 9 ) reported the necessity of careful evaluation for life-threatening diseases in cases with fever during the COVID-19 pandemic era.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, oral, pharyngeal and cervical infections (e.g., PA, tonsillitis, acute epiglottitis, deep neck abscess) may be overlooked if a thorough oral and pharyngo-laryngeal evaluation is avoided due to the high transmissibility of COVID-19. Akiyama et al ( 9 ) reported the necessity of careful evaluation for life-threatening diseases in cases with fever during the COVID-19 pandemic era.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of using personal protective equipment and isolation to prevent exposure to aerosols containing SARS-CoV-2, as well as the restriction of transoral procedures to severe cases (e.g., airway obstruction) has been highlighted in the COVID-19 pandemic era ( 2 ). Although COVID-19 can be easily diagnosed with rapid tests, co-infection with life-threatening oral, pharyngeal and laryngeal infections may be underdiagnosed due to insufficient oral examination ( 9 ). These diseases should not be overlooked due to the lack of appropriate evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…On the final day of this lockdown, 16,820 COVID-19 related hospital deaths were recorded [ 7 ]. The pressure experienced by the healthcare system may have resulted in collateral damage with regard to other patients, particularly for those with serious or urgent diseases [ 1 , 8 ]. Moreover, many patients have been hesitant to seek healthcare, a phenomenon described in the literature regarding the severe acute respiratory syndrome (SARS) epidemics [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 A reduction in the quality and quantity of care as a result of the extreme pressure experienced by the healthcare system may have resulted in collateral damage with regard to other patients, particularly for those with serious or urgent diseases requiring immediate treatment. 1,9,10 In addition, many patients have been hesitant to seek heath care during this period, a phenomenon briefly described in the literature regarding the shorter SARS epidemics. 11,12 To date, several works have alerted to an unexpected decrease in hospital admissions for non COVID-19 diseases, but very few have estimated this on a national level.…”
Section: Introductionmentioning
confidence: 99%
“…The care of non-COVID patients has certainly been impacted as a result. [1][2][3][4] The capacity of healthcare systems worldwide was rapidly overwhelmed following the beginning of the pandemic. France faced a shortage of both medical supplies and human resources during the first epidemic peak, in spring 2020, despite undertaking 55 days of national lockdown (from 17 March to 10 May 2020 included) .…”
Section: Introductionmentioning
confidence: 99%